Cellular solid-state nuclear magnetic resonance spectroscopy - Renault, Marie (National Academy of Sciences, 2012)
Decrypting the structure, function, and molecular interactions of complex molecular machines in their cellular context and at atomic resolution is of prime importance for understanding fundamental physiological processes. Nuclear magnetic resonance is a well-established imaging method that can visualize cellular entities at the micrometer scale and can be used to obtain 3D atomic structures under in vitro conditions. Here, we introduce a solid-state NMR approach that provides atomic level insights into cell-associated molecular components. By combining dedicated protein production and labeling schemes with tailored solid-state NMR pulse methods, we obtained structural information of a recombinant integral membrane protein and the major endogenous molecular components in a bacterial environment. Our approach permits studying entire cellular compartments as well as cell-associated proteins at the same time and at atomic resolution.